The Level of Vitamin D in Children and Adolescents with Nonalcoholic Fatty Liver Disease: A Meta-Analysis. (14th July 2019) - Zhu, Shanshan; Wang, Yuhui; Luo, Fei; Liu, Jie; Xiu, Liangchang; Qin, Jiheng; Wang, Tao; Yu, Na; Wu, Hongfu; Zou, Tangbin
Abstract : Background . The relationship between vitamin D level and NAFLD has not been investigated in children and adolescents. We performed a meta-analysis of published observational studies to assess this association between vitamin D levels (measured as serum 25-hydroxy vitamin D [25(OH)D]) and NAFLD in this age group. Methods . Relevant studies conducted before May 20, 2018, were identified from the following electronic databases: PubMed, the Cochrane Library, Embase, and the Chinese CNKI databases. The quality of the included studies was evaluated using the Newcastle Ottawa Scale, and associations between vitamin D levels and NAFLD were estimated using standardised mean differences (SMD) and 95% confidence interval (CI). Subgroup and sensitivity analysis were used to identify sources of heterogeneity, and publication bias was evaluated using funnel plots. Results . Eight articles were included in this meta-analysis. A significant difference was observed between low 25(OH)D levels and NAFLD in children and adolescents (SMD = -0.59, 95%CI = -0.98, -0.20, P <   0.01). Subgroup analysis revealed no differences in the study type, geographic location, BMI, and age subgroups. Conclusions . Low vitamin D levels were associated with NAFLD in children and adolescents.